2021
DOI: 10.1186/s12645-021-00083-x
|View full text |Cite
|
Sign up to set email alerts
|

Methylene blue associated with maghemite nanoparticles has antitumor activity in breast and ovarian carcinoma cell lines

Abstract: Background Cancer constitutes group of diseases responsible for the second largest cause of global death, and it is currently considered one of the main public health concerns nowadays. Early diagnosis associated with the best choice of therapeutic strategy, is essential to achieve success in cancer treatment. In women, breast cancer is the second most common type, whereas ovarian cancer has the highest lethality when compared to other neoplasms of the female genital system. The present work, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Various nanoparticles have been reported to induce ROS formation, eventually stimulating various anticancer events, such as oxidative stress, lipid peroxidation, DNA damage, and destabilization of mitochondria, resulting in cell death by apoptosis and necrosis ( Alharthy et al, 2022 ; Tabrez et al, 2022b ; Zughaibi et al, 2022 ). A low level of ROS has been suggested to regulate cancer cell tumorigeneses, whereas a high-level causes severe cellular damage ( Youhannayee et al, 2019 ; Silva et al, 2021 ). Some studies also indicated that treating cells with various stress factors, such as anticancer drugs, increases ROS levels and induces cellular apoptosis by triggering proapoptotic signaling molecules ( Lampiasi et al, 2009 ; Azizi et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Various nanoparticles have been reported to induce ROS formation, eventually stimulating various anticancer events, such as oxidative stress, lipid peroxidation, DNA damage, and destabilization of mitochondria, resulting in cell death by apoptosis and necrosis ( Alharthy et al, 2022 ; Tabrez et al, 2022b ; Zughaibi et al, 2022 ). A low level of ROS has been suggested to regulate cancer cell tumorigeneses, whereas a high-level causes severe cellular damage ( Youhannayee et al, 2019 ; Silva et al, 2021 ). Some studies also indicated that treating cells with various stress factors, such as anticancer drugs, increases ROS levels and induces cellular apoptosis by triggering proapoptotic signaling molecules ( Lampiasi et al, 2009 ; Azizi et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…To confirm that CHIKV AA and MAYV AA lost their ability to infect mammalian cells, including humans, these viruses and parental CHIKV and MAYV were inoculated on primary cultured human fibroblasts isolated from dental pulp [25]. Before that, to increase the inoculum pressure over fibroblasts, CHIKV AA /MAYV AA were grown in Aag-2 cells in T-75 flasks as described in the Methods section.…”
Section: Resultsmentioning
confidence: 99%
“…Vero cells were grown in Dulbecco's Modified Eagle Medium (DMEM) high glucose (Sigma-Aldrich) supplemented with 10% FBS and 1× P/S solution at 37 °C under 5% CO 2 . Human fibroblasts isolated from dental pulp were kindly supplied by Dr Sonia N. Bao and details can be seen elsewhere [25]. These cells were grown under the same conditions as Vero cells.…”
Section: Methodsmentioning
confidence: 99%
“…In order to measure the production of ROS, 4T1 cells were cultured in vitro and incubated with DZCP + (DZCP combined with ultrasonic treatment) under hypoxia (1% oxygen) conditions for 3 and 6 h, respectively. The ROS/hypoxia detection kit was used (Figure 3B), the characteristics of which are the same as the reported method (Silva et al, 2021;Zhang et al, 2021). The generated ROS was detected in DZCP + -treated cells with the appearance of green fluorescence, demonstrating that ROS generation and tumor cells decrease under hypoxic conditions.…”
Section: Intracellular Ros and Hypoxia Detectionmentioning
confidence: 96%